Longitudinal Study of Student Self-Regulation and Mental Health in Merdeka Digital Learning - Widyaningtyas, Prasita Ayu; Wirawati, Denik; Apriyanto, Sigit; Yuliana, Roma; Anum, Adelina (Journal Corner of Education, Linguistics, and Literature, 2025)
The rapid growth of digital learning within the Merdeka Curriculum has introduced new challenges concerning students’ digital wellbeing, self-regulation, and mental health. This study aimed to examine the longitudinal relationship among these variables among Year 10 students at SMA Negeri 9 Bandar Lampung over one semester. Employing a quantitative approach with repeated-measures design, data were collected at the beginning, middle, and end of the semester through structured questionnaires. The findings revealed a significant improvement in students’ digital wellbeing and self-regulation, accompanied by a gradual reduction in academic stress. Further analysis indicated that self-regulation acted as a mediating factor between digital wellbeing and mental health. These results support Zimmerman’s self-regulated learning theory and highlight the need to integrate digital literacy and self-regulation training within the implementation of the Merdeka Curriculum. Practically, the study provides insights for developing balanced learning strategies that promote both effective technology use and students’ psychological wellbeing in the digital era.